Teori Persaingan Sempurna Neoklasik Digugat - Lerbin R. Aritonang (Jurnal Ekonomi, 2006)
In 1995, Hunt and Morgan ( 1995) proposed a new theory of competition, namely the resource advantage theory of competition. The theory was explicatedÂ·and contrasted with the neoclassical theory of perfect competition. They argued that the new theory of competition explains key macro and micro phenomena better Than neoclassical competition theory. This article describes the new theory and responses of the scientific community.